Cechy reżimu odpływu rzek w zlewni Warty - Wrzesiński, Dariusz; Perz, Adam (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
This paper seeks to identify the features of the flow regime of the rivers in the basin of the river Warta in terms of the runoff, the structure as well as temporal and spatial variabilities. The analysis was carried out on the basis of hydrometric data from the Institute of Meteorology and Water Management from 1971-2010 obtained from 71 gauging stations located in 39 rivers. The research embraced the entire Warta basin with its tributaries. In hydrological terms, this region is characterized by sharp differences in the runoff conditions due to abundant or scarce water resources in the sub-basins. As a result, those rivers have different regime features; following the regularities in their flow variability, they can be classified into 3 types of the nival hydrological regime. The river Warta and its tributaries reveal exceptional differences in the total runoff, from the lowest values in Poland (under 100 mm, the upper Noteć basin) to very high in the upper Warta (above 380 mm, the Kręciwilk station). There are also big differences in the groundwater flow and its contribution to the total runoff. For some of them it exceeds 80%, the most distinct in Poland. The rivers of the Warta basin also show a wide range of variability in the discharges, from very stable to very irregular. In general, the greatest differences in the regime characteristics are between the central part of the basin in comparison with the northern and southern parts.
Keywords: river runoff; hydrological regime; the Warta basin